Present's ekphrasis: "Ciervos sobre una pared" by Jorge Guillén - Laplana Gil, José Enrique (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Commentary on the poem «Ciervos sobre una pared» (Clamor, 335) by Jorge Guillén as an example of ekphrasis.
Keywords: Jorge Guillén; Clamor; cave painting; ekphrasis